(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The Author meditates on the conflicting relationship between the State and territorial autonomies during the CoViD-19 emergency. He reflects on the emergency regulations through administrative orders enacted by regional and local authorities and the safeguard of the principle of unity and indivisibility of the Republic by the Government. He, also, thinks about the use of the principle of subsidiarity to entrust the management of the emergency to the State.